Prevalence of COVID-19 among healthcare workers before and after vaccination - Karina Pinheiro Teixeira dos Reis; Mirelle de Oliveira Saes; Ivy Bastos Ramis (Revista de Epidemiologia e Controle de Infecção)
Background and Objectives: healthcare workers are at high risk of acquiring infections during disease outbreaks. Therefore, this study aimed to determine the prevalence of COVID-19 among vaccinated and unvaccinated healthcare workers. Methods: a cross-sectional and observational study that assessed cases of flu syndrome that occurred between March 2020 and December 2021 in healthcare workers vaccinated and unvaccinated with CoronaVac or Astrazeneca in a hospital in the extreme south of Brazil. The study included cases of flu syndrome characterized and monitored by the institution’s occupational health sector and who underwent diagnostic tests by RT-PCR for SARS-CoV-2. The Prevalence Ratio estimated by Poisson regression analysis with variance adjustment was used to verify the factors and strengths of the associations. Results: a total of 1,088 cases of flu syndrome that occurred in healthcare workers between 2020 and 2021 were assessed. When adjusted for sex, age, role, sector, type of vaccine or previous diagnosis of COVID-19, the prevalence of COVID-19 among cases of unvaccinated workers was 51.5% (95% CI: 46.5- 56.5) and 32.1% (95% CI: 25.3-38.8) among unvaccinated workers. Moreover, COVID-19 vaccination reduced the prevalence of new infections by 33% (PR: 0.67; 95% CI: 0.56-0.81). Conclusion: COVID-19 vaccination significantly reduced the prevalence of COVID-19 among healthcare workers, regardless of sex, age, sector, role, type of vaccine or previous diagnosis of COVID-19.